PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STAD TERHADAP HASIL BELAJAR SISWA - Muhammad Ilyas; M. Dhafa Firdaus; Nurul Fatimah (PGMI Department of Universitas Islam Ibrahimy Banyuwangi, Indonesia, 2024)
This study was a quantitative research with a pre-experimental model using a One group pretest-posttest design. The population and sample of this study were all fifth-grade students at MI Al-Himmah, totaling 24 students. The instrument used as a data collection technique in this study was a student learning outcome test in the form of a pretest and posttest of 20 multiple-choice questions each, which had been previously tested for validity and reliability. The data analysis technique used in this study was a prerequisite test which included normality test, homogeneity test, and continued with hypothesis test using paired sample T test on SPSS version 27 application. The results of the study showed that the average posttest score of the students was higher than the average pretest score of the students. The average posttest score of the students was 80.42, while the average pretest score of the students was 52.92. Based on the results of hypothesis testing using paired sample t test on SPSS 27 application, the value of sig. 2-tailed was less than the value of Î± (0.05) with a significance level of 95% (0.000 < 0.05). This indicates that in this study, the alternative hypothesis (Ha) was accepted and it was stated that there was a significant effect of the Student Teams Achievement Division (STAD) cooperative learning model on the learning outcomes of fifth-grade students in the subject of IPAS at MI Al-Himmah in the 2023/2024 school year. After further hypothesis testing, an effect size test was conducted using Cohen's d to determine the magnitude of the effect. Based on the effect size test, the value of Cohen's d was 2.350. Referring to the guidelines for interpreting the effect size test, it was stated that the value of Cohen's d was in the very large category, so it was stated that the effect of the STAD cooperative learning model on the learning outcomes of fifth-grade students in the subject of IPAS was very large.